Grammatical Analysis on Abstract Translation Indonesian to English - Muhammad Faiz Azmi; Rahmanti Asmarani (UPT P2M Politeknik Negeri Malang, 2021)
Translation is a process that is almost unavoidable for both lecturers and students. This is true especially in writing scientific papers that must be written in English. The purpose of this study is to find out the grammatical errors present in the translation of abstracts. The data for this study were obtained from the abstracts written by non-English students of Dian Nuswantoro University. This analysis is qualitative research in nature. As for calculating the number of grammatical errors, quantitative methods were used. In this case, qualitative descriptive analysis in this study was a method that aimed to describe or provide an overview of an object of study investigated through samples or data that have been collected. The finding of this study revealed that some grammatical errors still occur including addition, omission and misinformation.